Respuesta :
49 - 4 = 45
7² - 2² = 45
a² - b² = ( a + b ) ( a - b ) - difference of squares
( 7 - 2 ) · ( 7 + 2 ) = 45
5 · 9 = 45
45 = 45
Answer: A ) Difference of Squares
7² - 2² = 45
a² - b² = ( a + b ) ( a - b ) - difference of squares
( 7 - 2 ) · ( 7 + 2 ) = 45
5 · 9 = 45
45 = 45
Answer: A ) Difference of Squares
Answer:
Option A is correct
Difference of squares identity should be used to prove 49-4 =45
Step-by-step explanation:
Prove that : 49 - 4 = 45
Polynomial identities are just equations that are true, but identities are particularly useful for showing the relationship between two apparently unrelated expressions.
Difference of the squares identity:
[tex]a^2-b^2 = (a-b)(a+b)[/tex]
Take LHS
49 - 4
We can write 49 as [tex]7 \times 7 =7^2[/tex] and 4 as [tex]2 \times 2 =2^2[/tex].
then;
[tex]49 - 4 = 7^2 -2^2[/tex]
Now, use the difference of square identity;
here a =7 and b = 2
[tex]7^2-2^2 = (7-2) \cdot (7+2)[/tex]
or
[tex]7^2-2^2 = 5 \cdot 9 = 45[/tex] = RHS proved!
therefore, the difference of square polynomial identity should be used to prove that 49-4 =45